Pengaruh Produksi Batubara terhadap Indeks Pembangunan Manusia di Provinsi Penghasil Batubara - Sembiring, Thomas Robiana; Wikarya, Uka (https://jurnal.binamandiri.ac.id/, 2025)
Coal mining is an essential component of natural resource (NR) management that supports Indonesia’s economy. However, as a non-renewable resource, its utilization must be optimized to contribute to human resource (HR) development. This study aims to examine the effect of coal production on the Human Development Index (HDI) as a benchmark for HR development. The objective is to assess the extent of the mining sector’s contribution and to identify further measures that can be taken to promote HDI improvement. Accordingly, this research seeks to ensure that coal-producing regions can develop high-quality human resources capable of sustaining post-mining economic growth. The study employs coal production, reflected in the Gross Regional Domestic Product (GRDP) of the coal and lignite mining sector, as the independent variable. Control variables include non-coal GRDP, local government expenditure on economic functions, health functions, and education functions, while HDI serves as the dependent variable. Using panel data from 2011 to 2020, the analysis applies a panel regression approach with the Least Square Dummy Variable (LSDV) estimation model. The findings reveal that coal production has a negative effect on HDI, whereas non-coal GRDP and local government expenditure on health functions have a positive effect on HDI.